Outcomes from a group intervention for coping with HIV/AIDS and childhood sexual abuse: reductions in traumatic stress. - Sikkema, Kathleen J; Hansen, Nathan B; Kochman, Arlene; Tarakeshwar, Nalini; Neufeld, Sharon; Meade, Christina S; Fox, Ashley M (AIDS and behavior, 2007)
Childhood sexual abuse is common among HIV-infected persons, though few empirically supported treatments addressing sexual abuse are available for men and women with HIV/AIDS. This study reports the outcome from a randomized controlled trial of a group intervention for coping with HIV and sexual abuse. A diverse sample of 202 HIV-positive men and women who were sexually abused as children was randomly assigned to one of three conditions: a 15-session HIV and trauma coping group intervention, a 15-session support group comparison condition, or a waitlist control (later randomly assigned to an intervention condition). Traumatic stress symptoms were assessed at baseline and post-intervention, with analysis conducted for the three-condition comparison followed by analysis of the two-condition comparison between the coping and support group interventions. Participants in the coping group intervention exhibited reductions in intrusive traumatic stress symptoms compared to the waitlist condition and in avoidant traumatic stress symptoms compared to the support group condition. No differences were found between the support group intervention and waitlist conditions. Tests of clinical significance documented the meaningfulness of change in symptoms.
Keywords: Acquired Immunodeficiency Syndrome; Adaptation, Psychological; Adult; Child; Child Abuse, Sexual; Crime Victims; Female; HIV Infections; Humans; Male; New York City; Psychotherapy, Group; Stress Disorders, Post-Traumatic; Urban Population